Moral Enhancement, Freedom, and the God Machine - Vagena, Dimitra (Conatus - Journal of Philosophy, 2018)
Greek translation of Julian Savulescu and Ingmar Persson, "Moral Enhancement, Freedom, and the God Machine," The Monist 95, no. 3 (2012): 399-421.